Comparing the electrochemical degradation of the fluoroquinolone antibiotics norfloxacin and ciprofloxacin using distinct electrolytes and a BDD anode: evolution of main oxidation byproducts and toxicity - Carneiro, Jussara F.; Aquino, Jose M.; Silva, Bianca F. [UNESP]; Silva, Adilson J.; Rocha-Filho, Romeu C. (Elsevier B.V., 2020)
The effects of the supporting electrolytes (SEs) Na2SO4, NaCl, Na2CO3, NaNO3, and Na3PO4 on the anodic oxidation of norfloxacin (NOR) and ciprofloxacin (CIPRO), assessed by the respective degradation kinetics and byproducts and electrolyzed solution antimicrobial activity, are compared. Galvanostatic anodic oxidations were performed in a filter-press flow cell fitted with a boron-doped diamond anode. Removal rates higher than the theoretical one for a process purely controlled by mass transfer were found for all SEs, indicative of contribution by indirect oxidation processes. However, the removal rates for NaCl were about tenfold higher, with the lowest energy consumption per order (ECO) of targeted pollutant removal rate (ca. 0.7 kW h m(-3) order(-1)), a very competitive performance. The TOC removal rates were also affected by the SE, but not as markedly. The antimicrobial activity of the electrolyzed solutions against Escherichia coli showed distinct temporal profiles, depending on the fluoroquinolone and SE. For instance, when Na3PO4 was used, the antimicrobial activity was completely removed for NOR, but none for CIPRO; conversely, when NaCl was used, complete removal was attained only for CIPRO. From LC-MS/MS analyses of Na3PO4 electrolyzed solutions, rupture of the fluoroquinolone ring leading to byproducts with no toxicity against E. coli occurred only for NOR, whereas exactly the opposite occurred for the NaCl solutions. Clearly, the nature of both the SE and the fluoroquinolone influence the oxidation steps of the respective molecule; this was also evidenced by the distinct short-chain carboxylic acids identified in the degradation of NOR and CIPRO.
Keywords: Fluoroquinolone electrooxidation; Boron-doped diamond anode; Anodic oxidation; Indirect mediated oxidation; Antimicrobial activity against E. coli; Electrooxidation byproducts